Characteristics of Farmers and Production of Sheep Dung as Organic Fertilizer For Food Crops In Kisar Island - W. Patty, Christian; Melkianus Puttileihalat, Paulus; Melianus Ririmase, Pieter (Devotion : Journal of Research and Community Service, 2022)
Characteristics of breeders determine sheep farming activities. Breeders are expected to always be able to improve their knowledge in carrying out various business activities, especially in utilizing the production of sheep dung to be used as organic fertilizer for plants. The purpose of this study was to determine the characteristics of farmers and the potential for production of sheep dung for food crops, especially corn. The method used in this study is a qualitative descriptive approach for breeder characteristics and the availability of sheep manure as a potential organic fertilizer measured through adult sheep that excrete manure per day or for 24 hours, then multiplied by the existing livestock population. The results showed that 44% of farmers aged 31-50 years, 56% had elementary school education, 65%, farmers as a main job 65% and farmers only as a sideline 11%, and the priority scale of farmers doing this activity is first to increase income, producing organic fertilizer , as traditional livestock and for savings. The production of sheep manure for one year is 11,711,609 tons/head/year, but the utilization rate for corn food crops is only 372,736 tons/year so that the excess is 11,338.873 tons/year due to its use only on corn and not on corn. other plants